Biofuels and food prices: Searching for the causal link - Andrea Bastianin; Marzio Galeotti; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2013)
We analyze the relationship between the prices of ethanol, agricultural commodities and livestock in Nebraska, the U.S. second largest ethanol producer. The paper focuses on long-run relations and Granger causality linkages between ethanol and the other commodities. The analysis takes possible structural breaks into account and uses a set of techniques that allow to draw inferences about the existence of long-run relations and of short-run in-sample Granger causality and out-of-sample predictive ability. Even after taking breaks into account, evidence that the price of ethanol drives the price dynamics of the other commodities is extremely weak. It is concluded that, on the basis of a formal, comprehensive and rigorous causality analysis we do not find evidence in favour of the Food versus Fuel debate.
Keywords: C22; C53; Q13; Q42; Q47; 330; Ethanol; Field Crops; Granger Causality; Forecasting; Structural Breaks